Phase II trial of daratumumab with DCEP in relapsed/refractory multiple myeloma patients with extramedullary disease - Ja Min Byun; Chang-Ki Min; Kihyun Kim; Soo-Mee Bang; Je-Jung Lee; Jin Seok Kim; Sung-Soo Yoon; Youngil Koh (Journal of Hematology & Oncology, 2022)
Key points 1. This is one of the very few prospective trials focusing on refractory multiple myeloma with extramdedullary disease (EMD). 2. We successfully laid grounds for implementing immunochemotherapy in EMD treatment.